Development of Ti microalloyed high strength steel plate by controlling thermo-mechanical control process schedule. (4th December 2017) - Xia, Jinian; Huo, Xiangdong; Li, Liejun; Peng, Zhengwu; Chen, Songjun
Abstract: In this study, the TMCP parameters including non-recrystallization temperature (Tnr) and optimal isothermal temperature were determined by thermal simulation experiments, and a new Ti microalloyed high strength steel plate was developed by controlling thermo-mechanical control process (TMCP) schedule. The effects of TMCP process on microstructural features, precipitation behavior and mechanical properties of Ti microalloyed high strength steel plate were investigated. The results revealed that the double-stage rolling process consist of rolling in the γ recrystallization region and the γ non-recrystallization region was benefical to promoting the mechanical properties of Ti microalloyed steel by achieving grain refinement. It was also found that large amounts of fine TiC (<10 nm) particles were precipitated during the isothermal treatment at 600 °C, which generated a 215 MPa precipitation strengthening effect.